Team nursing as a strategic response to the global nursing workforce shortage: challenges, opportunities and future directions - N. Muruganandan; Ivan Abhishek Prakash; Tanusri Mandal; Mayavati Baban Tupere; V. Manjula; Bhagirath Ram Bishnoi; Jyoti Katiyar; Golda Sahaya Rani R.; Deeksha Shukla; Niharika Mishra; Deepa N. R.; Mohammed Umar (International Journal of Research in Medical Sciences, 2026)
The global nursing workforce shortage threatens patient safety, healthcare quality, workforce sustainability, and progress toward universal health coverage. Although expansion of nursing education and recruitment remains essential, increasing workforce numbers alone cannot provide an immediate solution to persistent shortages, maldistribution, burnout, turnover, skill-mix imbalances, and increasing clinical complexity. Team nursing, a collaborative care-delivery model in which nursing personnel with complementary competencies provide coordinated care under registered nurse leadership, has re-emerged as a potentially valuable workforce strategy. This narrative review examines the contemporary relevance of team nursing, its potential contribution to workforce optimization, associated implementation challenges, and future directions. Current evidence suggests that appropriately designed team nursing may improve workload distribution, optimize skill utilization, support novice nurses, strengthen collaboration, and increase organizational flexibility. However, poorly implemented models may contribute to fragmented care, communication failures, role ambiguity, inappropriate delegation, and excessive supervisory burden. Team nursing should therefore not be interpreted as a substitute for adequate staffing or as a mechanism for replacing registered nurses with less-qualified personnel. Its effectiveness depends on acuity-informed staffing, competency-based delegation, clear accountability, stable team composition, supportive leadership, and structured communication. Future models should integrate real-time workload assessment, digital coordination, competency mapping, and continuous outcome monitoring while preserving registered nurse accountability. Team nursing may serve as a pragmatic component of broader workforce reform, but its success depends on context-sensitive implementation, protection of professional nursing expertise, and rigorous evaluation.